Modeling of an Air Conditioning System with Geothermal Heat Pump for a Residential Building. (25th February 2013) - Cocchi, Silvia; Castellucci, Sonia; Tucci, Andrea
Abstract : The need to address climate change caused by greenhouse gas emissions attaches great importance to research aimed at using renewable energy. Geothermal energy is an interesting alternative concerning the production of energy for air conditioning of buildings (heating and cooling), through the use of geothermal heat pumps. In this work a model has been developed in order to simulate an air conditioning system with geothermal heat pump. A ground source heat pump (GSHP) uses the shallow ground as a source of heat, thus taking advantage of its seasonally moderate temperatures. GSHP must be coupled with geothermal exchangers. The model leads to design optimization of geothermal heat exchangers and to verify the operation of the geothermal plant.